Ovis dalli subsp. dalli - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2011)
207. Dall’s Sheep Ovis dalli French: Mouflon de Dall / German: Dall-Schaf / Spanish: Carnero de Dall Other common names: Alaskan White Sheep (dall), Stone's Sheep (stone) Taxonomy. Ovis montana dalli Nelson, 1884, Yukon, Alaska. Microsatellite data provide some support for recognizing two subspecies. Subspecies and Distribution. O.d.dalliNelson,1884—Alaska,Canada(YukonTerritory,extremeWNorthwestTerritoriesandextremeNWBritishColumbia). O.d. stonei]A. Allen, 1897 — Canada (Yukon Territory, N British Columbia). Descriptive notes. Hentbods 130-178 cm (males) and 132-162 cm (females), tail, 8-13 cm (males) and 8-10 cm (females), shoulder height 91:6-109 cm (males) and 78.7-88. 9 cm (females), hindfoot 38-46 cm (males) and 28-41 cm (females); weight, males average 81-7 kg (up to 136 kg) and females 56-8 kg. Dall’s Sheep are either entirely off-white, occasionally with a black tail (dalli), or highly variable (stonei), from pale brown to grayish or blackish-brown in body color, with white underparts, white face, grizzled neck, and distinct rump patch or with darker hairs on cheeks, throat, and neck. In the palest individuals, dark hairs are restricted to a saddle-patch down each side and the outer sides of the foreand hindlegs. The subspecies intergrade and color variations occur within the same population. Diploid chromosome number is 54. Habitat. Dall’s Sheep habitats consist of steep, rugged terrain adjacent to alpine, subalpine, and at lower elevations even forested areas that in winter have light snowfall and wind-blown sites cleared of snow that allow access to forage. Cold winter temperatures well below 0°C and windy conditions prevail. Gray Wolves (Canis lupus) and Coyotes (C. latrans) are the principal predators, but predation is not normally a major mortality factor. Food and Feeding. They are principally grazers; in one study, annual diets consisted of 81-5% grasses and sedges. In other studies, winter diets consisted of 87-6% graminoids, 3% forbs, and 8:5% shrubs and summer diets consisted of 57% ...